Using School Code of Conduct as an Antidote to Learner Indiscipline: Reflections from Secondary School Motheo, Free State. - Letuma, Motsekiso; Mdodana-Zide, Lulama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Order in schools and classrooms is essential for successful teaching and learning because it enables teachers and learners to devote time to learning activities. However, learners' indiscipline continues to surge despite various interventions. This study explored how secondary schools' learner code of conduct is implemented to alleviate disciplinary issues. The study was grounded on the assertive discipline theory and employed an interpretive paradigm using a qualitative approach through a case study research design. Data was obtained using semi-structured interviews administered to six school management team members and focus group interviews with seven teachers from four purposefully selected quintile-three secondary schools. The findings revealed that schools use the learner school code of conduct to address and reduce instances of indiscipline. This is done by orally presenting it to learners The study concludes that teachers believe secondary learners already know how to behave, and their duty is to remind them of what is expected. The study recommends that teachers avoid assumptions that secondary school learners already know how to behave. A shift in implementing the learner school code of conduct to a more proactive approach that upholds principles of positive discipline is also recommended